Customer, Corporation, and Cause: A Comprehensive Model of Cause Selection in Cause-Related Marketing. Issue 3 (3rd July 2019) - Fazli-Salehi, Reza; Torres, Ivonne M.; Angel Zúñiga, Miguel
Abstract: When developing corporate social responsibility programs, marketing practitioners have to choose the domain of their activities. Whether they should decide to focus on education, healthcare, air pollution, or other fields is always a matter of discussion among marketing experts, brand managers, and board members. The selection of a domain for cause-related marketing is contingent on a variety of variables. Many scholars have studied the potential influential factors that might play a role in the success of a cause-related marketing topic, yet a comprehensive model has not yet been presented. This article will develop a model of cause-related marketing domain selection based on three dimensions—corporate, cause, and customer dimension—and will offer an argument on the area of cause-brand fit. The article will then propose several future research areas.